PENGARUH KOMITE AUDIT, PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU DALAM PELAPORAN KEUANGAN - Giovanni, Virgin; ., Mahroji (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to see the effect of the audit committee, profitability, company size on timeliness in financial reporting. This research consists of three independent variables namely Audit Committee which is proxied by Dummy, Profitability which is proxied by ROA and Company Size which is proxied by Size and has one dependent variable namely Timeliness which is proxied by Dummy. In this study, there were 24 companies that had been selected using purposive sampling criteria with a total of 72 objects studied at LQ45 companies during the period 2019 to 2021. The data used is secondary data in the form of financial reports obtained from the website www.idx.co.id measured using the SPSS27 research tool with Logistic Regression analysis. The results of this study indicate that the Audit Committee and Profitability variables have a significant positive effect on the timeliness of financial reporting, while company size has no significant effect on the timeliness of financial reporting. The Nagelkerke R Square value is 43.9% of the variable audit committee, profitability and company size while the remaining 56.1% is influenced by variables outside this study.